ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

Blocking GPR15 Counteracts Integrin-dependent T Cell Gut Homing in Vivo - Schramm, Sebastian; Liu, Lijuan; Saad, Marek; Dietz, Lisa; Dedden, Mark; Müller, Tanja; Atreya, Imke; Bosch-Voskens, Caroline; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Journal of Crohns & Colitis, 2024)
Background and Aims: The G protein coupled receptor GPR15 is expressed on and functionally important for T cells homing to the large intestine. However, the precise mechanisms by which GPR15 controls gut homing have been unclear. Thus, we aimed to elucidate these mechanisms as well as to explore the potential of targeting GPR15 for interfering with T cell recruitment to the colon in inflammatory bowel disease [IBD]. Methods: We used dynamic adhesion and transmigration assays, as well as a humanised in vivo model of intestinal cell trafficking, to study GPR15-dependent effects on gut homing. Moreover, we analysed GPR15 and integrin expression in patients with and without IBD, cross-sectionally and longitudinally. Results: GPR15 controlled T cell adhesion to MAdCAM-1 and VCAM-1 upstream of α4β7 and α4β1 integrin, respectively. Consistently, high co-expression of these integrins with GPR15 was found on T cells from patients with IBD, and GPR15 also promoted T cell recruitment to the colon in humanised mice. Anti-GPR15 antibodies effectively blocked T cell gut homing in vitro and in vivo. In vitro data, as well as observations in a cohort of patients treated with vedolizumab, suggest that this might be more effective than inhibiting α4β7. Conclusions: GPR15 seems to have a broad, but organ-selective, impact on T cell trafficking and is therefore a promising target for future therapy of IBD. Further studies are needed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: adhesion; GPR15; Inflammatory bowel disease; T cell homing; vedolizumab

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Etrolizumab-s fails to control E-Cadherin-dependent co-stimulation of highly activated cytotoxic T cells - Wiendl, Maximilian; Dedden, Mark; Liu, Lijuan; Schweda, Anna; Paap, Eva-Maria; Ullrich, Karen; Hartmann, Leonie; Wieser, Luisa; Vitali, Francesco; Atreya, Imke; Müller, Tanja; Günther, Claudia; et al. (Nature Communications, 2024)
Despite promising preclinical and earlier clinical data, a recent phase III trial on the anti-β7 integrin antibody etrolizumab in Crohn’s disease (CD) did not reach its primary endpoint. The mechanisms leading to this outcome are not well understood. Here we characterize the β7+ T cell compartment from patients with CD in comparison to cells from individuals without inflammatory bowel disease. By flow cytometric, transcriptomic and functional profiling of circulating T cells, we find that triple-integrin-expressing (α4+β7+β1hi) T cells have the potential to home to the gut despite α4β7 blockade and have a specific cytotoxic signature. A subset of triple-integrin-expressing cells readily acquires αE expression and could be co-stimulated via E-Cadherin-αEβ7 interactions in vitro. Etrolizumab-s fails to block such αEβ7 signalling at high levels of T cell stimulation. Consistently, in CD patients treated with etrolizumab, T cell activation correlates with cytotoxic signatures. Collectively, our findings might add one important piece to the puzzle to explain phase III trial results with etrolizumab, while they also highlight that αEβ7 remains an interesting target for future therapeutic approaches in inflammatory bowel disease.
CRIS-Team Scopus Importer:2024-02-16

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02